(untitled) (European Journal of Education and Psychology, 2010)
Universities for older people are currently one of the most popular programs for active ageing Spain. Older people’s participation in such programs has repercussions, not only in the improvement of their integration and social activity, but also in that learning at these ages produces benefits in physical and mental health. Thus, the goal of our investigation is to analyze these benefits in daily memory (spatial, linguistic, sequential, and of things) from attending the University for Older People. For this purpose, the sample is made up of two groups, one from the University for Older People, who have been attending it for more than five years (N= 264), and a group of people over 50 years who do not attend the University for Older People (N= 453). In a comparison of both groups, the results show that the students from the University for Older People obtain significantly lower global scores in daily memory, linguistic memory, sequential memory and memory of things.